A comparative examination of instructional methods in team and solo sports - Mavropulo O.S. ,; Demyanova L.M. ,; Tashchiyan A.A. ,; Zhikharev D.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to discern the distinctive aspects of training in team and individual sports. Methods and structure of the study. To accomplish this objective, a combination of quantitative and qualitative analytical techniques and statistical analysis was employed. The research was conducted in a series of steps: data gathering and processing, summarizing the findings, and drawing conclusions. Results and conclusions. Several key differences in approaches to training athletes in team and individual disciplines have been identified. Mainly, team sports require an emphasis on tactical training and player interaction, while individual disciplines are focused on developing the technique of performing a specific element and managing the athlete's psycho-emotional state.